One step away from Morris-Garner: Wrotham park damages in Singapore - YIP, Man (Institutional Knowledge at Singapore Management University, 2020)
Remarkably, within the same year, the highest appellate courts in the UK and Singapore have for the first time handed down landmark decisions on Wrotham Park damages (see Wrotham Park Estate Co v Parkside Homes Ltd [1974] 1 W.L.R. 798; [1974] 2 All E.R. 321) for breach of contract. Decided about four months apart, the cases of Turf Club Auto Emporium Pte Ltd v Yeo Boong Hua [2018] SGCA 44 and Morris-Garner v One Step (Support) Ltd [2018] UKSC 20; [2018] 2 W.L.R. 1353 took different paths in their treatment of such damages. Whilst both decisions confirm the compensatory nature of the awards and limit their availability, the Singapore Court of Appeal considered the English limiting criterion—requiring that the breach of contract results in a loss of an economically valuable asset created or protected by that contractual right—to be too uncertain. This note discusses the Singapore case. It examines if the Singapore divergence from English law is a step in the right direction and its further implications.